بناء انموذج مقترح للارشاد الديني الوقائي من الابتزاز الالكتروني من وجهة نظر المرشدين التربويين (Journal of the College of Basic Education, 2024)
The current research aimed at building a proposed model for preventive religious guidance in reducing electronic extortion and evaluating the program by identifying the opinions of educational counselors in it. The model of the program, including the t-test for two samples to extract the distinction of the paragraphs, the t-test for one sample, chi-square and other statistical methods. The results of the research showed that the proposed preventive religious counseling program, according to the educational counselors, has an effectiveness and ability to reduce electronic extortion. The researcher reached a set of recommendations and proposals.The opening words: "Preventive religious counseling program, electronic extortion".